Comprehensive Land Consolidation and Linear Cultural Heritage Protection, Utilization, Cohesion and Integration: A Case Study of the Gutian Section of the Meiguan Historical Trail, South China Historical Trail, Guangdong Province - Wu Jialong; Li Hongju; Deng Ting; Luo Sihua; Hu Jie; Zhang Zijian; Niu Chengyu; Wang Kai; Jiang Yan; Su Shaoqing (Redai dili, 2024)
The protection of historical and cultural heritage sites is the main focus of land space planning and use control. Its protection and utilization are important for promoting the revitalization of rural culture and building a pattern of historical and cultural protection, and are essential for the research on comprehensive land consolidation in recent years. The historical trail of South China is a linear cultural heritage site of Guangdong's historical development. Exploring the connotative relationship between comprehensive land consolidation and the protection and utilization of linear cultural heritage is conducive to enhancing their synergy and superposition. This study begins with a connotation analysis and trend analysis of comprehensive land consolidation and linear cultural heritage protection and utilization, taking the connecting line of the Gutian section of the ancient Meiguan historical trail of the Southern China historical trail in Guangdong Province as an example to explore the working relationship between comprehensive land consolidation and the protection and utilization of linear cultural heritage. It proposes a comprehensive land consolidation path for linear cultural heritage protection and utilization. Results showed that: 1) The problems faced by the protection of historical trails were closely related to the goal and content of comprehensive land consolidation; 2) The protection of historical trails and the comprehensive land consolidation could be integrated into the implementation of land space planning, rights and interests protection, policy incentives, public participation and landscape coordination to jointly promote the enhancement of land space value; 3) Focusing on the dimensions of development orientation, planning layout, engineering design, overall planning funds and service operation, it is necessary to constantly innovate the path of comprehensive land improvement across the region, and comprehensively promote the protection and utilization of rural cultural heritage. Guangdong Province can fully utilize the platform tools of comprehensive land consolidation in the protection of South China historical trail, achieve the connection and integration of ancient cultural protection and utilization with land consolidation projects, and establish a mutual feedback relationship in work, innovate and establish a working mechanism for the integration and development of comprehensive land consolidation and historical trail protection, which is conducive to the synergistic effect of rural revitalization and historical and cultural protection, better service and support for rural revitalization and high-quality development.